Hubungan antara pengetahuan sikap dan tindakan dengan kesadaran bencana pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi - Pasla, Gersom Figo Chrystianto; Wariki, Windy Mariane Virenia; Rombot, Dina Victoria (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: Indonesia is one of the most disaster-prone countries in the world. Indonesia has a high potential for disasters so it is important that people have the right knowledge, attitudes and actions in dealing with disaster awareness that can occur at any time which has a serious impact, especially in public health issues, for example the number of fatalities, serious injuries, psychiatric trauma, increased risk of infectious diseases. Aim: To determine the relationship between knowledge, attitudes, and actions with disaster awareness in students of the Faculty of Medicine, Sam Ratulangi University. Methods: The type of research used is quantitative with an observational analytic approach with a cross-sectional design. The sampling technique used simple random sampling and the research instrument used was a questionnaire. Results: This study included as many as 206 respondents. The results showed that most students of the Faculty of Medicine, Sam Ratulangi University had moderate knowledge with disaster awareness as much as 58.7%, high attitudes with disaster awareness as much as 67.0%, and moderate actions with disaster awareness as much as 52.4%. Conclusion: There is no relationship between knowledge and action and disaster awareness in the Faculty of Medicine of Sam Ratulangi University students, and there is a relationship between attitude and disaster awareness in the students. Keywords: disaster awareness, knowledge, attitude, actions